2014
DOI: 10.1371/journal.pone.0091586
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Anthropometric Indices of Adiposity against Whole-Body Magnetic Resonance Imaging – A Study within the German European Prospective Investigation into Cancer and Nutrition (EPIC) Cohorts

Abstract: BackgroundIn epidemiological studies, measures of body fat generally are obtained through anthropometric indices such as the body mass index (BMI), waist (WC), and hip circumferences (HC). Such indices, however, can only provide estimates of a person’s true body fat content, overall or by adipose compartment, and may have limited accuracy, especially for the visceral adipose compartment (VAT).ObjectiveTo determine the extent to which different body adipose tissue compartments are adequately predicted by anthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 38 publications
1
49
0
3
Order By: Relevance
“…Finally, we found that BMI in either cohort did not moderate the increased leptin among schizophrenia participants in our results. Although the leptin profile is intimately linked to various parameters of adiposity (total body fat, percentage body fat and fat distribution), these are not necessarily directly reflected in parameters such as BMI (Neamat-Allah et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we found that BMI in either cohort did not moderate the increased leptin among schizophrenia participants in our results. Although the leptin profile is intimately linked to various parameters of adiposity (total body fat, percentage body fat and fat distribution), these are not necessarily directly reflected in parameters such as BMI (Neamat-Allah et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These include subcutaneous adipose tissue, which is located under the skin and stores $80% of total body fat with the major stores found in the upper (abdominal, subscapular fat) and lower body (gluteal-femoral fat). Intraabdominal adipose tissues include the visceral adipose tissue located around the digestive organs (mesenteric and omental) and the retroperitoneal depot (kidney), which together account for $20% of total body fat 6,7 (Fig. 1A).…”
Section: Adipose Tissue Localization and Compositionmentioning
confidence: 99%
“…Notwithstanding the fact that anthropometric indices strongly correlate with total and subcutaneous body fat volumes, we [8] and others have previously demonstrated that single or combined anthropometric measures only inadequately reflect visceral fat volume as objectively determined by MRI [9][10][11][12][13][14][15]. Thus, the underestimation of disease risks associated with visceral adiposity in epidemiological studies relying on anthropometry remains crucial, while the use of anthropometric indices only for individual risk assessment in clinical practice may lack sensitivity.…”
Section: Introductionmentioning
confidence: 80%
“…For the present analyses on circulating markers and visceral fat, MRI parameters and blood samples were available for 592 subjects. Further details about the background of this sub-study have been described previously [8]. In brief, the sub-sample was recruited according to a rectangular sampling scheme by age group, and sex, with the participation rate being 47 %.…”
Section: Study Populationmentioning
confidence: 99%